The Effectiveness of Election Administrative Law Enforcement by the General Election Supervisory Agency - Bahari Bahari; Laode Bariun; Winner Agustinus Siregar (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
This research examines the the effectiveness of election administration law enforcement by the General Election Supervisory Agency in the application of Law no. 7 of 2017 concerning Elections related to handling violations, namely Article 461 paragraph 6 and Article 464 of Law Number 7 of 2017 in handling administrative violations in the 2019 Election at Southeast Sulawesi. With the various forms of Administrative Election violations found in the 2019 General Election, it takes hard work from the Election Supervisory Agency (Bawaslu) to handle administrative violations in order to create the 2019 Election that is fair, honest, and free of various kinds of violation. The method of this research uses empirical normative legal research with a statue approach. The results showed that administrative violations processed by Bawaslu of Southeast Sulawesi Province reflect the effectiveness of the application of Article 461 paragraph 6 and Article 464 of Law Number 7 of 2017 in handling administrative violations in the 2019 Election at Southeast Sulawesi. Bawaslu of Southeast Sulawesi Province has handled 5 (five) administrative violations with verdicts that do not meet the formal and material requirements, 2 (two) administrative violations with a verdict not proven legally and a verdict proven legally. This achievement is an effective performance of making verdict that lead to doing things right, which contributes to fulfill mission or achieve goals of agency. The violation was caused by the reported party's unconsciousness that it qualifies as a violation and the reported lack of awareness in implementing direct, general, free, confidential, honest and fair in the administration of elections. From the aspect of legal culture, the general public or the parties misunderstand that their actions are classified as violatios in election.